Value Creation in Indian Paper Industry: An Analysis - Sakthivel, N.; Arjunan, C. (Indian Journal of Finance, 2009)
Maximizing the shareholder value is considered as one of the fundamental goals of all businesses. In United States, top management is expected to maximize shareholder value. There are a number of value based management (VBM) frameworks. Shareholder value analysis (SVA) Rapport (1986) and Economic Value Analysis (EVA) developed by Stern Stewart (1990) are the two well-known ones. Maximizing shareholders value is becoming the new corporate standard in India. The corporates, which gave the lowest preference to the shareholders' inquisitiveness, are now bestowing the utmost inclination to it. Shareholders' wealth is measured in terms of the returns they receive on their investment. The returns can either be in the form of dividends or in the form of capital appreciation or both. Capital appreciation in turn depends on the subsequent changes in the market value of shares. This market value of shares is influenced by a number of factors, which can be company specific, industry specific and macro-economic in nature.